Methylphenidate abuse and misuse in patients affected with a psychiatric disorder and a substance use disorder: a systematic review - Chiappini, Stefania; Gramuglia, Pietro Domenico; Mosca, Alessio; Cavallotto, Clara; Miuli, Andrea; Corkery, John Martin; Guirguis, Amira; Schifano, Fabrizio; Martinotti, Giovanni (Frontiers in Psychiatry, 2024)
BackgroundMethylphenidate (MPH), a central nervous system stimulant primarily prescribed for attention-deficit/hyperactivity disorder (ADHD), has seen increasing rates of misuse and abuse, particularly in patients with dual diagnosis (co-occurring psychiatric disorders and substance use disorders/SUDs). The heightened risk of dependence and adverse effects in these vulnerable populations warrants a systematic review to assess the prevalence and pattern of abuse/misuse of MPH among patients within this population and to understand potential risk factors, patterns of misuse, and outcomes, including the impact on psychiatric symptoms and overall mental health, the effects on SUD (e.g., exacerbation or mitigation of symptoms), and the incidence of adverse events and complications (e.g., cardiovascular issues, psychological effects).MethodologyA systematic review was conducted in August-September 2024 using both PubMed and Scopus databases. The following search strategy was used: TITLE-ABS-KEY (methylphenidate OR Ritalin OR Concerta) AND TITLE-ABS-KEY (abuse OR misuse OR dependency OR addiction) AND TITLE-ABS-KEY (dual diagnosis OR comorbid psychiatric disorder OR psychiatric disorder AND substance use disorder). The systematic review was structured in accordance with the PRISMA guidelines and identified studies were assessed by title/abstract and full text screening against eligibility criteria.ResultsA total of 12 studies were selected for analysis after screening for relevance, quality, and adherence to inclusion criteria. Findings indicated that individuals with psychiatric disorders, particularly conduct disorder (N=593/1551 individuals), mood disorder (N=90/1551 individuals), anxiety disorder (N=66/1551 individuals), personality disorder (N=44/1551 individuals) and major depression disorder (N=40/1551 individuals), were more likely to misuse MPH. Co-occurring SUD, especially involving Alcohol Use Disorder (N=475/1551 individuals), Cannabis Use Disorder (N=371/1551 individuals), Nicotine Use Disorder (N=343/1551 individuals), Cocaine Use Disorder (N=68/1551 individuals), significantly elevated the risk. Misuse often involved higher doses than prescribed (N=84/1551 individuals) or using non-oral routes of administration (N=20/1551 individuals; e.g., snorting). Adverse outcomes included heightened risk of gastrointestinal events (N=201/1551 individuals), cardiovascular events (N=108/1551 individuals), psychosis (N=69/1551 individuals), and exacerbation of psychiatric symptoms (N=1082/1551 individuals).ConclusionMPH misuse and abuse are significant concerns in patients with psychiatric disorders and SUD. Risk factors include impulsivity, history of substance abuse, and access to prescription stimulants. Integrated therapeutic approaches and stricter prescription monitoring are recommended to mitigate misuse risks.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024576724.